2011
DOI: 10.1002/chem.201100016
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids with Hydrogen‐Bonding Side Chains have an Intrinsic Tendency to Sample Various Turn Conformations in Aqueous Solution

Abstract: Local structure in unfolded proteins, especially turn segments, has been suggested to initiate the hierarchical protein-folding process. To determine the intrinsic propensity to form such turn structures, amide I' band profiles of the Raman, IR, and vibrational circular dichroism (VCD) spectra, and several structure-sensitive NMR J-coupling constants, have been measured for a series of GxG (x=D, N, T, C) peptides, in which the central x residues are abundant in various turn motifs in folded proteins. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
160
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(181 citation statements)
references
References 51 publications
14
160
2
Order By: Relevance
“…Derived ΔG values for PII to β transitions show a good correlation to those derived for dipeptides23. We have detected significant turn structures in AcGNPNH 2 , AcGTPNH 2 and AcGDPNH 2 (pH = 2 and 6)44. Results from this study have broad implications on the early-stage events of protein folding.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Derived ΔG values for PII to β transitions show a good correlation to those derived for dipeptides23. We have detected significant turn structures in AcGNPNH 2 , AcGTPNH 2 and AcGDPNH 2 (pH = 2 and 6)44. Results from this study have broad implications on the early-stage events of protein folding.…”
Section: Resultssupporting
confidence: 68%
“…The smaller 3 J αN values for AcGXGNH 2 are consistent to X samples all three major backbone conformations in AcGXGNH 2 , while X samples only PII and β conformations in AcGXPNH 2 (Thr, Asn and Asp are excluded). For AcGXPNH 2 (X = Thr, Asn and Asp), X is expected to form turn structures44; it explains smaller observed 3 J αN values for these residues in AcGXPNH 2 compared to those in AcGXGNH 2 . For all other amino acids, contents of α conformations in AcGXGNH 2 can be calculated from equation (1), in which 3 J αN (α) is assigned to be 4.11 Hz, corresponding to a ϕ value of −60° (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…19 For further details of the (u,w) 2 -motifs see Hollingsworth et al 19 (B) The natural distributions of residues occurring in select (u,w) 2 -motif contexts (colored dots) are displayed with that full dataset as a background (gray) and the relevant basins from A outlined for reference. The colored distributions correspond to residues from some of the most prominent (u,w) 2 While much work has been done on the relationships between amino acid sequence and conformation, [13][14][15][16] less has been done to explore the details of how the conformation of a residue depends on the conformation of its neighboring residues, irrespective of amino acid type. 13,17,18 Recently, we published a study of local protein conformations that focused on what we called (u,w) 2 -motifs; each such motif corresponds to a particular path of four sequential Caatoms-named residues i to i 1 3 -that is defined by the conformations of the two central residues: 19 In that study, we developed a list of the 101 most common (u,w) 2 -motifs that occur in proteins.…”
Section: (A)]mentioning
confidence: 99%
“…The populations of each group are as follows: aXa-59,596; aXb-7,951; aXd-6,160; aXP II -7,073; bXa-3,601; bXb-34,525; bXd-8,480; bXP II -12,846; dXa-11,253; dXb-6,203; dXd-3,933; dXP II -4,552; P II Xa-3,897; P II Xb-11,877; P II Xd-6,659; P II XP 198. Low contour levels in the observed distributions are colored blue (0-10), light brown (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), green (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and white (31-40). Higher contours then use a repeated pattern of teal, orange, blue, red, green, and purple for every additional 10 observations.…”
Section: The Influence Of Conformational Contextmentioning
confidence: 99%
“…Thus, the fact that the 3 J HNa coupling constants of the dipeptides are distributed in the range from 5.5 to 9.6 Hz indicates that the backbone conformations of dipeptides are mixtures of PP II and b-strand structures consistent with the experimental finding by Avbelj et al (2006) who showed that the fractional populations of PP II and b-strand conformations are dominant in 19 blocked amino-acids (N-acetyl-X-N 0 -methylamide) except for Gly. In our previous work, we also showed that the CD spectra of the blocked dipeptides can be described as a linear combination of the CD eigenspectra of the PP II and bstrand conformations (Oh et al 2010(Oh et al , 2012 and further examined the validity of a two-state approximation by comparing our results with previous works done by other groups (Hagarman et al , 2011. However, it should also be emphasized that the fitting analysis method using reference values of two representative conformations such as PP II and b-strand is intrinsically approximate in nature.…”
Section: Resultsmentioning
confidence: 74%